Determination of the time of death of a domestic cat by measuring the area of a wet spot - D. Shkundia; J. Serdioucov (Ukrainian Journal of Veterinary Sciences, 2024)
Animal cruelty is a criminal offence under the current legislation of Ukraine. When investigating criminal proceedings related to animal cruelty, including domestic cats, it is often necessary to establish the time of death. Therefore, the development of new methods for determining it and improving existing ones is extremely relevant. The purpose of the study was to establish the relationship between the obtained values of wet spot area indicators and the time of death. To achieve this goal, the authors propose a new method for determining the age of death of domestic cats based on the results of measuring the area of a wet spot obtained from skeletal muscle tissue samples of corpses (Shkundia method). To do this, samples of muscle tissue were taken from the corpses of cats, a wet spot preparation was obtained by pressing and its area was calculated to establish a correlation between the values of this indicator and the time that has passed since death. The study of the obtained indicators established that these values are constant, and the features of fluctuations in the values of this indicator with the time elapsed since the death of the animals were established and shown graphically. Using a number of statistical methods, the absence of dependence of wet spot area indicators on the muscles from which samples were taken for research and animal breeds was determined. The nature of changes in the values of the wet spot area indicator depending on time is established and the features of their fluctuations in different periods during 27 days from the moment of animal death were explained. Reference values of these indicators depending on the time elapsed since the death of animals are presented, which can be used by forensic veterinary experts in practical work to determine the time of the occurrence of death of domestic cats. Due to a number of advantages, this method can be widely implemented in the practice of forensic veterinary medicine